Design of tree topology based Byzantine fault tolerance system - Wei-dong LYU; Xue-guang ZHOU; Zhi-min YUAN (Tongxin xuebao)
A tree topology based Byzantine fault tolerance system was designed and the calculation of the Byzantine node bound based on depth and width was given.The consistency protocol was designed through divide the tree into groups by communication and work,which guaranteed the safety of system.The access of a node was determined with joint signature mechanism.The Byzantine nodes were placed to the leaves by view change protocol,which guaranteed the liveness of the system.On the foundation of traditional protocol,the new protocol support multiple tasks operating at the same time,and communication between nodes is largely decreased,as well as the space complexity,hence the feasibility being promoted,and the gap between Byzantine fault tolerance system and the non-Byzantine systems being narrowed.